Regional energy eco-innovation sector as a driver of post-war development of Ukraine's economy - O.A. Borodina (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2022)
Consolidation with European social, economic and environmental programs in the framework of Ukraine's integration into the European energy space has become extremely important given the growing threats to energy security and should become the basis for postwar greening of regional and national innovation systems in the context of decrabicization, carbon Alternative Energy Sources. With the use of empirical and theoretical methods, a retrospective and generalization of Ukraine's rankings and global world innovation rankings was conducted. Applying the method of comparing the regions of the country by the level of innovation of enterprises and extrapolating these results to the share of such enterprises in the total number of industrial entities in the regions helped to identify their lack of correlation and emphasize the lack of stable dependence of industrial development and innovation. The article contains a number of methods: general, special and interdisciplinary, which allowed to screen areas for the most favorable development of the postwar economy, taking into account the synergistic component of regional development and achieve the goal of the study. The aim of the article is to analyze the innovative component of regional and national economic development for the implementation of decarbonization and energy green transition in Ukraine; substantiation of the world's leading imperatives and national directions of effective post-war integration into relevant European programs. An analysis of Ukraine's rating status in several international indices of environmental efficiency and innovation activity of regions was shown, which showed the lack of correlation between regions of Ukraine, which actualizes the search for the most effective drivers of economic development for Ukraine's postwar development models. At the same time, it is the consolidation of efforts of national stakeholders of innovative development of the country with relevant European institutions, in particular, in the direction of greening regional economic systems, will ensure postwar development of innovative regions and industries, which in turn will be drivers of related territories and industries, while ensuring a synergistic effect.